2013
DOI: 10.1021/jp403746m
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Studies of BH4 Reorientations and Li Diffusion in LiLa(BH4)3Cl

Abstract: To study the reorientational motion of BH 4 groups and the translational diffusion of Li + ions in the novel bimetallic borohydride chloride LiLa(BH 4 ) 3 Cl, we have measured the 1 H, 11 B, and 7 Li NMR spectra and spin−lattice relaxation rates in this compound over the temperature range of 23−418 K. At low temperatures (T < 110 K), the proton spin− lattice relaxation rates are governed by fast reorientations of BH 4 groups. This reorientational process can be satisfactorily described in terms of a two-peak d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 59 publications
5
98
1
Order By: Relevance
“…ions are disordered and occupy two-thirds of the available positions and are found to be a new series of fast Li-ion conductors for metal borohydrides, as was originally reported in h-LiBH 4 [81] Structural investigation using theoretical DFT methods suggests that the structures are stabilized by higher entropy rather than lower energy [40]. Solid-state NMR spectroscopy reveals a ''paddle wheel'' mechanism for the ion conductivity [42]. Furthermore, anion substitution in lithium borohydride significantly improves the lithium ion conductivity for LiBH 4 because the hexagonal structure may be stabilized at RT [82,83].…”
Section: New Properties Of Metal Borohydrides-towards Multi-functionamentioning
confidence: 81%
See 1 more Smart Citation
“…ions are disordered and occupy two-thirds of the available positions and are found to be a new series of fast Li-ion conductors for metal borohydrides, as was originally reported in h-LiBH 4 [81] Structural investigation using theoretical DFT methods suggests that the structures are stabilized by higher entropy rather than lower energy [40]. Solid-state NMR spectroscopy reveals a ''paddle wheel'' mechanism for the ion conductivity [42]. Furthermore, anion substitution in lithium borohydride significantly improves the lithium ion conductivity for LiBH 4 because the hexagonal structure may be stabilized at RT [82,83].…”
Section: New Properties Of Metal Borohydrides-towards Multi-functionamentioning
confidence: 81%
“…Three classes of metal borohydride chlorides with fully ordered structures have been identified so far: the mono metallic borohydride halide Sr(BH 4 )Cl [37], bimetallic KZn(BH 4 )Cl 2 [15] and rare earth containing LiM(BH 4 ) 3 Cl, M = La, Ce, Pr, Nd, Gd, and Sm [38][39][40][41][42] [44]. Furthermore, substitution of BH 4 -with Cl -can also take place in the novel metal borohydrides formed during mechanochemical synthesis; for example, Rietveld refinement suggests incorporation of *42 mol% of Cl -on one of the two BH 4 -sites in Al 3 Li 4 (BH 4 ) 13 [45].…”
Section: Metal Borohydride Halidesmentioning
confidence: 99%
“…Another class of materials to be considered is rare earth (RE) borohydrides, with hydrogen capacities varying between 9.0 wt % for Y(BH 4 ) 3 and 5.5 wt % for Yb(BH 4 ) 3 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Li-containing RE borohydrides are also considered as solid state electrolytes for new battery applications, due to their high Li-ion conductivities [20][21][22][23]. RE borohydrides have shown novel properties such as luminescence, and a magnetocaloric effect has also been recently published [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent interest in utilizing LiBH 4 as a solid-state electrolyte was established through the work of Orimo [4], who demonstrated that the ionic conductivity of lithium can be greater than 1 mS/cm at temperatures above the orthorhombic to hexagonal phase transition that occurs at 380 K [5]. This work has been expanded to achieve high conductivity in LiBH 4 based solid electrolytes through the addition of Li halide salts [6][7][8], nanoconfinement [9][10][11][12], nanoionic destabilization [13,14], ion substitution [15][16][17][18][19][20][21], and eutectic formation [22].…”
Section: Introductionmentioning
confidence: 99%